Slade house : a novel - Mitchell, David (David Stephen) (Random House, 2015)
"Down the road from a working-class British pub, along the brick wall of a narrow alley, if the conditions are exactly right, you'll find the entrance to Slade House: a surreal place where visitors see what they want to see, including some things that should be impossible. Every nine years, the house's residents--an odd brother and sister--extend a unique invitation to someone who's different or lonely: a precocious teenager, a divorced policeman, a shy college student. But what really goes on inside Slade House? For those who find out, it's already too late" --